Comparison Study of the Adsorption of Copper Ions By Activated Carbon and A Locally Collected Bentonite - Abraheem A. M; Emad A. S. AL-Hyali; Alaa A.Azeez (College of Education for Pure Sciences, 2013)
Abstract In this study, a locally collected bentonite and activated carbon (AC) synthesized from spent lubricant oils by chemical treatment were used as new non conventional and low cost adsorbents for the copper (Cu+2) ions adsorption in a batch mode at various initial concentrations and different temperatures. Systematic studies on Cu+2 ions adsorption equilibrium and kinetics by both adsorbents were carried out. The investigation were performed at different initial concentrations of Cu+2 ions (10, 20, 30, 40, 50, 60 mg/L), contact time (10-90 min), and temperatures (25-55 °C). Depending on the results of temperature effect, thermodynamic parameters (ΔG°, ΔH and ΔS°) were estimated from two sources. First; from the adsorption distribution constant (Kd) which is represented by the ratio between the adsorbed and remained Cu+2 ions in solution at equilibrium and second, from Freundlich isotherm constant (Kf). Comparable results are obtained. Freundlich and Langmuir isotherm models were applied to the adsorption data of the studied systems. The results obtained indicated that, the clay adsorbs Cu+2 ions more intense than AC, with higher maximum adsorption capacity. Langmuir isotherm is better fitted to the adsorption data of the study system than Freundlich isotherm. The effect of contact time data of Cu+2 ions adsorption onto clay, conducted at various initial concentrations were applied to pseudo first and second order kinetic models. The rate of adsorption was found to conform to pseudo second order kinetic with good correlation (R2>0.99) and consistent values of the experimental (qe(exp)) and calculated (qe(cal)) adsorption capacities. The initial rate of adsorption was found to increase with initial concentration, where as the over all rate constant exhibited opposite variation. The employed adsorbents might be successfully used for the removal of other heavy metal ions from industrial wastewater.